How to crochet - Turner, Pauline (New Yrok, NY Sterling Publishing Co., 2001)
The definitive crochet course complete with step-by-step techniques, stitch libraries and projects for your home and family.
D., 2005, unk
Keywords: Needle and handwork -- Crocheting; Crocheting